trans-Resveratrol Ameliorates Stress-Induced Irritable Bowel Syndrome-Like Behaviors by Regulation of Brain-Gut Axis - Xu, Ying; Cui, Su-Ying; Ma, Quan; Shi, Jing; Yu, Ying; Li, Jian-Xin; Zheng, Liang; Zhang, Yi; Si, Jian-Min; Yu, Ying-Cong (Frontiers in Pharmacology, 2018)
Background Irritable bowel syndrome (IBS) is a functional disorder characterized by abdominal pain and abnormalities in defecation associated with psychiatric disorders such as depression and anxiety due to the dysfunction of brain-gut axis. This study aims to determine whether trans-Resveratrol affects chronic-acute combined stress (CACS)-induced IBS-like symptoms including depression, anxiety and intestinal dysfunction. Methods ICR male mice were exposed to the CACS for 3 weeks. trans-Resveratrol were administrated daily (2.5, 5 and 10 mg/kg, i.g.) 30 minutes before CACS. Behavioral tests were performed to evaluate the treatment effects of trans-Resveratrol on IBS. Hippocampus tissues were collected and processed Golgi staining and immuno-blot analysis. Ileum and colon tissues were collected and processed Hematoxylin and Eosin staining and immuno-blot analysis. Results Administration with trans-Resveratrol before CACS for 3 weeks significantly reversed CACS-induced depression- and anxiety-like behaviors and intestinal dysfunction in mice, which implied a crucial role of trans-Resveratrol in treatment of IBS-like disorder. Furthermore, trans-Resveratrol improved hippocampal neuronal remodeling, protected ileal and colonic epithelial barrier structure against CACS insults. The further study suggested that trans-Resveratrol normalized phosphodiesterases 4A (PDE4A) expression and CREB-BDNF signaling that were disturbed by CACS. The increased pCREB and BDNF expression in the hippocampus were found, while decreased pCREB and BDNF levels were observed after treatment with trans-Resveratrol. Conclusions The dual effects of trans-Resveratrol on stress-induced psychiatric and intestinal dysfunction may be related to normalization of PDE4A expression and subsequent pCREB-BDNF signaling in the hippocampus, ileum and colon.